Le bruit des avions comme facteur de dépréciations immobilières, de polarisation sociale et d’inégalités environnementales. Le cas d’Orly - Guillaume Faburel; Isabelle Maleyre (Développement Durable et Territoires)
Finding conciliations between large infrastructures of transport and their surrounding area emerges as an important goal of sustanaible development strategies and rests on a better knowledge of their environmental and territorial effects. We report here an Hedonic Price Method (HPM) application to housing values and household mobility, for eight cities located near to Orly Airport and exposed to aircraft noise. Results show that aircraft noise causes property values depreciation, and that the Noise depreciation Index is growing since 1995, even with a noise exposure level remaining stable. Moreover, household mobility shows that newcomers are younger and of lower social level than leaving ones. Hence, crossing these results lets have a glimpse of increasing environmental inequities, for more modest households will have in the future to endure more important depreciations.